A stochastic Gronwall inequality in random time horizon and its application to BSDE - Hun O; Mun-Chol Kim; Chol-Kyu Pak (Journal of Inequalities and Applications, 2020)
Abstract In this paper, we introduce and prove a stochastic Gronwall inequality in an (unbounded) random time horizon. As an application, we prove a comparison theorem for backward stochastic differential equation (BSDE for short) with random terminal time under a stochastic monotonicity condition.